2013
DOI: 10.1158/1078-0432.ccr-12-2334
|View full text |Cite
|
Sign up to set email alerts
|

SLC1A5 Mediates Glutamine Transport Required for Lung Cancer Cell Growth and Survival

Abstract: Purpose: We have previously identified solute-linked carrier family A1 member 5 (SLC1A5) as an overexpressed protein in a shotgun proteomic analysis of stage I non-small cell lung cancer (NSCLC) when compared with matched controls. We hypothesized that overexpression of SLC1A5 occurs to meet the metabolic demand for lung cancer cell growth and survival.Experimental Design: To test our hypothesis, we first analyzed the protein expression of SLC1A5 in archival lung cancer tissues by immunohistochemistry and immu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
277
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(291 citation statements)
references
References 36 publications
11
277
1
2
Order By: Relevance
“…55 Finally, our data indicate that blocking Gln uptake could be, possibly in association with other approaches, a suitable target to inhibit MM cell growth as also reported for other hematologic malignancies. 23,24,27 In line with this hypothesis, we show that bortezomib increased the cytotoxic effect of E. chrysanthemi ASNase as previously reported for acute leukemia cells. 56 Others recently showed that CB-839 blocks MM growth and synergized with pomalidomide in a preclinical model, 57 and a phase 1 trial with CB-839 in patients with R-MM is currently under investigation.…”
Section: Discussionsupporting
confidence: 91%
“…55 Finally, our data indicate that blocking Gln uptake could be, possibly in association with other approaches, a suitable target to inhibit MM cell growth as also reported for other hematologic malignancies. 23,24,27 In line with this hypothesis, we show that bortezomib increased the cytotoxic effect of E. chrysanthemi ASNase as previously reported for acute leukemia cells. 56 Others recently showed that CB-839 blocks MM growth and synergized with pomalidomide in a preclinical model, 57 and a phase 1 trial with CB-839 in patients with R-MM is currently under investigation.…”
Section: Discussionsupporting
confidence: 91%
“…First, ASCT2, the Na + -dependent neutral amino acid transporter encoded by SLC1A5, is broadly expressed in lung cancer cell lines and accounts for a majority of glutamine transport in those cells (Figure 1). It has been shown that γ-L-glutamylp-nitroanilide (GPNA) inhibits this transporter and limits lung cancer cell growth (73). Additional interest in GPNA lies in its ability to enhance the uptake of drugs imported via the monocarboxylate transporter MCT1.…”
Section: Pharmacological Strategies To Inhibit Glutamine Metabolism Imentioning
confidence: 99%
“…Other research identified microenvironment-related pathways important for lung tumor growth and progression. These pathways included Rab27a (39), SLC1A5 (40), and vascular endothelial growth factor receptor (VEGFR)-2/epidermal growth factor receptor (EGFR) (41). In a recent perspective, Stathopoulos and Kalomenidis note and review the importance of tumor-host interactions in the formation of malignant pleural effusions (42).…”
Section: Tumor Microenvironmentmentioning
confidence: 99%